2002
DOI: 10.1124/dmd.30.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Brimonidine into Anterior and Posterior Tissues of Monkey, Rabbit, and Rat Eyes

Abstract: ABSTRACT:The objectives of the study were to evaluate the distribution of brimonidine (␣ 2 -adrenergic agonist) into anterior and posterior ocular tissues. Single or multiple doses of a 0.2 or 0.5% brimonidine tartrate solution were administered to one or both eyes of monkeys or to one eye of rabbits. Brimonidine was administered intraperitoneally to rats. After topical administration, [14 C]brimonidine was rapidly absorbed into the cornea and conjunctiva and distributed throughout the eye. [ 14 C]Radioactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 18 publications
(14 reference statements)
5
72
0
2
Order By: Relevance
“…1). The observed kinetic pattern was consistent with those obtained in previous studies after single instillations of bunazosin, 16) flunarizine, 17) brimonidine, 18) and timolol. 19) In the presence of PLA at 5 mg/ml, pyridoxamine and FD-4 concentrations at 30 min after single instillation were increased 29-and 16-fold, respectively (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…1). The observed kinetic pattern was consistent with those obtained in previous studies after single instillations of bunazosin, 16) flunarizine, 17) brimonidine, 18) and timolol. 19) In the presence of PLA at 5 mg/ml, pyridoxamine and FD-4 concentrations at 30 min after single instillation were increased 29-and 16-fold, respectively (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that for topically applied drugs, the route of drug delivery to ciliary body and retina is through conjunctiva and sclera. Since these tissues have rich network of capillaries, it is likely that in our study, the presence of dye in these tissues is subsequent to systemic absorption (Chien et al, 1990;Acheampong et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Já foi descrito que a pigmenta ção iriana pode influenciar no efeito de drogas antiglaucomatosas, pois tecidos pigmentados obtiveram maior concentração da droga, e redução mais lenta da mesma (27,28) . Em seu estudo Kim et al, relata que a durabilidade da ação dos colírios nesta população é diferente, sendo maior com Alphagan ® (Allergan, Irvine, CA) e que a ação de pico é semelhante entre os colírios (23) .…”
Section: Discussionunclassified